2015
DOI: 10.1021/acs.bioconjchem.5b00178
|View full text |Cite
|
Sign up to set email alerts
|

EDB Fibronectin Specific Peptide for Prostate Cancer Targeting

Abstract: Extradomain-B fibronectin (EDB-FN), one of the oncofetal fibronectin (onfFN) isoforms, is a high-molecular-weight glycoprotein that mediates cell adhesion and migration. The expression of EDB-FN is associated with a number of cancer-related biological processes such as tumorigenesis, angiogenesis, and epithelial-to-mesenchymal transition (EMT). Here, we report the development of a small peptide specific to EDB-FN for targeting prostate cancer. A cyclic nonapeptide, CTVRTSADC (ZD2), was identified using peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 31 publications
5
118
0
Order By: Relevance
“…A small cyclic nonapeptide ZD2 of the sequence of CTVRTSADC was recently identified using peptide phage display to target EDB. This peptide demonstrated excellent specific targeting to tumor in vivo 101 . Another class of FN-targeting ligands is the peptides that target fibronectin-fibrin complexes.…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 96%
See 1 more Smart Citation
“…A small cyclic nonapeptide ZD2 of the sequence of CTVRTSADC was recently identified using peptide phage display to target EDB. This peptide demonstrated excellent specific targeting to tumor in vivo 101 . Another class of FN-targeting ligands is the peptides that target fibronectin-fibrin complexes.…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 96%
“…Even though limited studies have been done with a specific focus on FN-targeting optical imaging probe for in vivo cancer imaging 101, 125 , FN-targeting fluorescent probes have been developed in most studies for validating tumor targeting efficiency of the ligands. The probes also have been tested for in vivo diagnosis of other diseases, including rheumatoid arthritis, atherosclerosis, etc.…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 99%
“…It is found that efficient accumulation of the targeted contrast agent was observed in the tumour area at 5 min, however the contrast continuously decreased faster after 5 min for SGd than VGd. Previously, the other peptides used for MRI targeting imaging, including CREKA, ZD2 and CLT1, also indicated similar findings that agents modified with targeting peptides would provide enhanced contrast and also slower contrast decrease with scanning time 2,11,21 . As illustrated in Scheme 1, the VGd, once injected via tail vein, circulated in the blood vessel and conveniently bound to the VEGFR2 highly expressed in tumours, resulting in the improved tumour uptake of VGd compared with SGd.…”
Section: Discussionmentioning
confidence: 54%
“…Extradomain B-fibronectin (EDB-FN) is a cancer-related fibronectin isoform highly expressed in the ECM of various aggressive human cancers, but not in normal tissues [19, 20]. It is a marker of epithelial-to-mesenchymal transition (EMT) and plays a key role in EMT induction, cancer cell stemness, cancer proliferation, and angiogenesis.…”
Section: Mr Molecular Imaging Of Abundant Oncoproteins Using Small Momentioning
confidence: 99%